Evaluation of Heat-Treated AISI 316 Stainless Steel in Solar Furnaces to Be Used as Possible Implant Material - Milosan, Ioan; Florescu, Monica; Cristea, Daniel; Voiculescu, Ionelia; Pop, Mihai Alin; Cañadas, Inmaculada; Rodriguez, José; Bogatu, Cristina Aurica; Bedo, Tibor (MDPI AG, 2020)
The appropriate selection of implant materials is very important for the long-term success of the implants. A modified composition of AISI 316 stainless steel was treated using solar energy in a vertical axis solar furnace and it was subjected to a hyper-hardening treatment at a 1050 °C austenitizing temperature with a rapid cooling in cold water followed by three variants of tempering (150, 250, and 350 °C). After the heat treatment, the samples were analyzed in terms of hardness, microstructure (performed by scanning electron microscopy), and corrosion resistance. The electrochemical measurements were performed by potentiodynamic and electrochemical impedance spectroscopy in liquids that simulate biological fluids (NaCl 0.9% and Ringer’s solution). Different corrosion behaviors according to the heat treatment type have been observed and a passivation layer has formed on some of the heat-treated samples. The samples, heat-treated by immersion quenching, exhibit a significantly improved pitting corrosion resistance. The subsequent heat treatments, like tempering at 350 °C after quenching, also promote low corrosion rates. The heat treatments performed using solar energy applied on stainless steel can lead to good corrosion behavior and can be recommended as unconventional thermal processing of biocompatible materials.